Web based LIS education : potentials and feasibility of regional models - Petr, Kornelija; Vrana, Radovan; Aparac, Tatjana (2002)
Distance education has been attracting attention of librarians’ associations and educators for more than 60 years, even more since the advent of the Internet. With its rapid expansion in the 1990s, distance education got new means for its realization. In Croatia the Internet is getting more accessible at many access points. One such point is Croatian Academic and Research Network (CARNet), that supports distance education in several ways. There are many topic and issues in relation to the concept of distance education that can be accomplished in electronic environment. This is also valid for the LIS Continuing Professional Development (CPD) in Croatia and wider region. Thus, the paper offers a review of challenges and possible models of LIS Web based CPD in Croatia, as well as plans for further cooperation among interested countries in the wider region.
ENG